THE POSSIBILITIES OF USING AND PROSPECTS FOR THE DEVELOPMENT OF CAM SYSTEMS (E Conference Zone, 2022)
Analyses and determinations of the main directions and principles of development of CAM systems when processing blanks on CNC machines are given in the article